Slovenija na stiku velikih evropskih pokrajinskih enot - Perko, Drago (Traditiones (Ljubljana), 1997)
Slovenia has an area of only 20,272 km2. In the world there are about 150 bigger and only 50 smaller countries. However, thanks to the fact it is located on the very spot in Central Europe where major geographical units (the Alps, the Dinaric Mountains, the Pannonian Plain and the Adriatic Sea) intersect and interwine, few countries, even much bigger ones, can compete with Slovenia as far as landscape variety is concerned. Diversity and the transit character of its regions are Slovenia's main geographical features which give the country its recognizable identity.
Keywords: geografija; geography; regional geography; regionalna geografija; Slovenia; Slovenija; regionalizacija